PENGARUH PEMBIAYAAN KESEHATAN, TENAGA KESEHATAN, PENDAPATAN PER KAPITA TERHADAP KASUS KEMATIAN BAYI DI KOTA PONTIANAK - Dian Syahtilawati, B61111050 (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACT The background of this research are on health financing, health workers, income per capita, and infant mortality cases. This study aims to analyze the simultaneousus and partial effects of health care costs, the number of health workers and per capita incometo infant mortality cases in the city of Pontianak. This study uses panel data from 6 districts in the city of Pontianak during 2008 – 2012. The independent variables in the study are health financing / health center budget, the number of health workers, per capita income as an independent variable. The dependent variable is the cases of infant mortality. Multiple linear regression analysis is carried out to test the hypothesis. The study shows that health financing / health center budgets, the number of health workers and per capita income have significantly simultaneouseffect to the cases of infant mortality. Partially, health financing / health center budgetsand per capita income afffect the case of infant mortality insignificantlyin the city of Pontianak. On the other hand, the number of health workers has significant partial effect on infant deaths in the city of Pontianak. To sum up, health financing/health centre budget and per capita income contribute insignificant effect on infant deaths. Health financing(health centers budgets) contribute more on the operational costs of health centers and health center services. Moreover, per capita income is used more on consumption rather than on health costs. In contrast, lack of health workers affects significantly to the cases infant deaths. Thus, allowing public to access public healthservices make the workers should be spread in every districts. Key words: health financing/ health centre budgets, the number of health workers, per capita income, infant mortality cases